Hukum Demokrasi Dalam Pelaksanaan Pilpres Dan Pilkada Pada Negara Sistem Presidensial - Destina Balqis Anggiyanti; Ruth Shelomita; Dhamara Kusuma Swastika P; Laga Sugiarto (Jurnal Hukum dan Sosial Politik, 2023)
. In the practice of democratic state administration, the presidential election and regional head elections are certainly one of the country's focuses in the future to find leaders who will take care of this nation, of course it is hoped that the elected leaders are leaders who really carry out this great mandate as well as possible. Based on the choice of the community, this leader will be elected through the democratic system of elections, but there are still many problems that often occur in its implementation. The purpose of this research is to analyze the law of democracy in the implementation of presidential and regional elections in a presidential system country. This research method is normative juridical research with the basis of research using a statutory approach. The results of this study are that the Presidential System, especially in Indonesia, is still often weakened by the provisions of public office and the constitution on the powers of the head of state and the law, supervision in the general election system must certainly be carried out as cleanly as possible in order to create leaders who really have high integrity.